Caloric effects in ferroic materials - Fähler, Sebastian; Pecharsky, Vitalij K. (MRS bulletin, 2018)
The fundamentals and applications of ferroic materials—ferromagnetic, ferroelectric, and ferroelastic—are common subjects discussed in just about every graduate course related to functional materials. Looking beyond today’s traditional uses, such as in permanent magnets, capacitors, and shape-memory alloys, there are worthwhile and interesting questions common to the caloric properties of these ferroic materials. Can ferroic materials be used in a cooling cycle? Why are these materials susceptible to external fields? Which combination of properties is required to make some of them suitable for efficient cooling and heat pumping? We address these questions in this introduction to ferroic cooling, which comprises magnetocaloric, electrocaloric, elastocaloric and barocaloric approaches and combinations thereof (i.e., multicalorics). These are addressed in greater detail in the articles in this issue.